2001
DOI: 10.1038/sj.gt.3301510
|View full text |Cite
|
Sign up to set email alerts
|

Liver-targeted gene transfer into a human hepatoblastoma cell line and in vivo by sterylglucoside-containing cationic liposomes

Abstract: The major limitations of viral vectors, particularly those related to safety and immunogenicity, have prompted studies to improve methods of non-viral gene delivery. 1Among such non-viral vectors, cationic liposomes are one of the more promising non-viral systems for use in gene therapy.2 The efficient delivery of functional therapeutic genes into target cells is an important problem in gene therapy approaches for the treatment of cancer and metabolic diseases, as well as human immunodeficiency virus infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…8,15) In both lipoplexes, the highest gene expression was observed at a charge ratio (Ϫ : ϩ) of 1.0 : 2.3 and transfection efficacy was reduced at higher charge ratios. This observation agrees with the previous reports about conventional lipoplex in various types of cells, 16,17) sterylglucoside-containing lipoplex in HepG2 cells, 18) and mannosylated lipoplex in macrophages by the uptake of mannose receptor. 19) As shown in Fig.…”
Section: Discussionsupporting
confidence: 83%
“…8,15) In both lipoplexes, the highest gene expression was observed at a charge ratio (Ϫ : ϩ) of 1.0 : 2.3 and transfection efficacy was reduced at higher charge ratios. This observation agrees with the previous reports about conventional lipoplex in various types of cells, 16,17) sterylglucoside-containing lipoplex in HepG2 cells, 18) and mannosylated lipoplex in macrophages by the uptake of mannose receptor. 19) As shown in Fig.…”
Section: Discussionsupporting
confidence: 83%
“…For liver gene delivery, in addition to generating liverspecific liposomes by labeling them with asialoglycoprotein receptor ligands, such as asialofetuin or steylglucoside, 16,17 portal vein administration of lipoplexes has been shown to be a more effective approach than systemic administration. 4 The present study also showed that a one-log level increase (2.4 Â 10 4 versus 2.4 Â 10 3 RLU/mg protein) in luciferase activity was achieved when lipoplexes were administered via portal vein compared to tail vein injection.…”
Section: Liposome-mediated Liver Gene Deliverymentioning
confidence: 99%
“…This method has proven to be a viable option for the clinical treatment of several diseases, including cystic fibrosis and cancer. 5,10,11 A second method used to enhance the specificity of gene therapy is by coupling cell-binding ligands, such as folic acid (FA), [12][13][14][15] transferrin 16 or carbohydrates 17 to liposomes for the purpose of combining the intrinsic activities of lipids with the receptor-mediated uptake properties of the applied ligand.…”
Section: Introductionmentioning
confidence: 99%